Influência da temperatura e do teor de WSx no comportamento tribológico e de oxidação em filmes finos de TIN + WSx depositados por magnetron sputtering reativo - Serra, Ediomar Costa (2019)
TiN+WSx coatings were deposited by reactive magnetron sputtering to investigate the influence of temperature and tungsten disulphide (WSx) on the tribological and oxidation behavior of this compound. The WSx contents used were 4; 19 and 40 at%, calculated by RBS. GIXRD analysis showed only peaks of the crystalline structure of TiN, without the presence of peaks characteristic of the WSx. The plan (111) had preferential orientation, with loss of intensity and discrete displacement of the peaks to smaller angles due to the incorporation of 4% WSx in the TiN matrix, resulting in an amorphous state for the other contents. The nanohardness showed a tendency to reduce its values as the WSx contents increased in the thinness of TiN thin films. The reciprocal tribological tests were performed against alumina sphere (Al3O2). At room temperature the coatings with 4 and 19 at% WSx had their coefficients of friction (μ) reduced in relation to pure TiN, with best result for 19 at%, which also exhibited a lower wear rate. The 40% WSx film despite having a low friction effect indicated failure of the coating before the end of the test due to its low hardness, resulting in an increase in the coefficient of friction and the rate of wear. The composition with 4 at% WSx showed a slight increase in the coefficient of friction, above 70°C, as well as in the wear rate, attributed to the increase in abrasion. The 19 at% WSx coating exhibited a low friction effect up to 12 min of the test performed at 150°C, and thereafter increased coefficient of friction, which reached an average value similar to the test at 300°C. Low wear rate values were recorded up to 70ºC, above that, a tendency was observed in the growth of the same due to the abrasive effects. The film with 40 at% of WSx showed similar tribological behavior to 70°C, showing increasing tendency in friction coefficient value and wear rate to higher temperatures.